Problematika Integrasi Masyarakat Muslim-Thai Dalam Negara Thailand - Supriati H. Rahayu; Taufik Nugroho; Muthmainnah Muthmainnah; Difla Nadjih; M. Parid; Nur Alfan Bahem (Universitas Cokroaminoto Yogyakarta, 2022)
The conflict between the Muslim-Thai community and the Royal Thai Government for quite a long time since the acquisition of Southern Thailand Muslim areas (Yala, Narathiwat, Pattani, Songkhla and Satun) from Britain into the Thai kingdom under the umbrella of the Anglo-Siamese Treaty 1909. This historical research intends to answer one question: why did the Muslim-Thai conflict with the Royal Thai Government drag on? As a result, the Thai Government's initial program was to build nationalism with a Buddhist state ideology through the use of the Thai language with the Thai Rathaniyom jargon, which means Thailand for the Thai people. Malay language is prohibited, Islamic educational institutions must follow national education standards. This is where the Muslim-Thai resistance begins. The resistance varied to voice the aspirations of Muslim-Thai residents in the South who wanted them to be given the authority to manage themselves.